2009
DOI: 10.1111/j.1440-1681.2008.05125.x
|View full text |Cite
|
Sign up to set email alerts
|

INERTIA OR INACTION? BLOOD PRESSURE MANAGEMENT AND CARDIOVASCULAR RISK IN DIABETES

Abstract: 1. Diabetes is a significant risk factor for cardiovascular disease (CVD), but the presence of comorbidities, such as hypertension, markedly increases CVD risk. The aim of the present study was to determine the effectiveness of hypertension management in patients with diabetes. 2. The cvTRAC Study was a cross-sectional study of CVD risk factors in primary care practices across Australia. General medical practitioners enrolled patients they considered to be at increased risk of CVD and reported on cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…61 Therapeutic inertia, whereby therapy is initiated but not subsequently modified when the patient remains uncontrolled, was identified as a major contributing factor for failure of patients with hypertension to meet BP targets in a cross-sectional study of 6603 men and 5896 women with diabetes in primary care in Australia. 62 In this study, therapeutic inertia was identified in > 73% of uncontrolled patients receiving treatment, compared with just 5.4% of uncontrolled patients identified as requiring treatment according to treatment guidelines but not receiving therapy -a significant therapeutic inertia gap. The authors surmised that current guidelines for controlling BP in patients with T2D have not been very effective in ensuring therapy is intensified or modified when treatment goals are unmet 62 i.e.…”
Section: Discussionmentioning
confidence: 95%
“…61 Therapeutic inertia, whereby therapy is initiated but not subsequently modified when the patient remains uncontrolled, was identified as a major contributing factor for failure of patients with hypertension to meet BP targets in a cross-sectional study of 6603 men and 5896 women with diabetes in primary care in Australia. 62 In this study, therapeutic inertia was identified in > 73% of uncontrolled patients receiving treatment, compared with just 5.4% of uncontrolled patients identified as requiring treatment according to treatment guidelines but not receiving therapy -a significant therapeutic inertia gap. The authors surmised that current guidelines for controlling BP in patients with T2D have not been very effective in ensuring therapy is intensified or modified when treatment goals are unmet 62 i.e.…”
Section: Discussionmentioning
confidence: 95%
“…1 Studies have suggested that clinical inertia, or provider failure to initiate or intensify hypertension therapy when indicated based on clinical guidelines, is a prime contributor to inadequate BP control. 2,3 One study examined Ϸ46 000 clinic visits and found that, in 87% of visits where patients had BP Ͼ140/90 mm Hg, providers did not intensify therapy. 4 Others have attempted to evaluate underlying causes for clinical inertia.…”
mentioning
confidence: 99%
“…Após análise de regressão logística, verificou-se que os fatores independentemente associados Tabela 3 -Fatores associados a não controlo tensional após análise de regressão logística, com risco relativo (odds ratio e intervalo de confiança (IC)) 35,36 Isto pode-se explicar pela menor utilização pelos homens dos cuidados de saúde e sua menor valorização destes cuidados e de estilos de vida saudáveis. 37,38 A formação académica esteve associada a maior controlo da TA, tal como noutros estudos 19,20 realizados em locais com níveis globais de baixo nível de formação e socio-económica.…”
Section: 34unclassified
“…22,[55][56][57] Ainda assim, há diversos estudos que reportam uma terapêutica não farmacológica insuficiente no que se refere a exercício físico em pessoas com diabetes, mostrando muito potencial de melhoria no seu controlo tensional. 36 Seria então esperada uma relação direta com o controlo tensional em pessoas com diabetes. Uma possível explicação para este resultado poderá estar relacionada com o facto da escala utilizada medir além do nível de atividade física também a motivação para o aumentar o que poderá levar a alguma inércia terapêutica, específica em doentes com maior motivação, esperando-se mais tempo até intensificação da terapêutica farmacológica.…”
unclassified